Analysing the expression of genes associated with induced resistance in potato plants treated with phosphites - Machinandiarena, M.F. (2009)
Phosphites (Phi) have the ability to protect plants against different pathogens, both through a direct effect in oomycete metabolism and by an indirect effect stimulating the plant´s natural defence responses. We have previously shown that KPhi foliar application to potato plants resulted in different protection levels against Phytophthora infestans depending on dose and plant age at application time. In order to identify genes that are involved in induced resistant in plants treated with KPhi, we analyzed by RT PCR, the time course of transcript levels of two genes which encode predicted transcription factors involved in pathogen perception and defence gene expression. Preliminary results showed that WRKY and NPR1 were differentially induced in plants both treated with Phi and infected with Phytophthora infestans, showing an earlier and highest induction than infected plants non treated with Phi. These results may allow us to hypothetize that Phi treatment might trigger a fast mechanism to protect potato plants to pathogen infections.